A comparison of the mechanical and corrosion behavior of Fe49.5Mn25Cr15Ni10C0.5 medium-entropy alloy with its subsystems steels. (December 2022) - Wei, Ran; Jiang, Zhen; Gao, Qiuyu; Chen, Chen; Zhang, Suo; Han, Zhenhua; Chen, Liangbin; Wang, Tan; Wu, Shaojie; Li, Fushan
Abstract: We systematically compared the mechanical and corrosion behavior of Fe49.5 Mn25 Cr15 Ni10 C0.5, a face-centered-cubic (FCC) medium-entropy alloy (MEA) with low-cost, with its subsystems steels (Fe74.5 Cr15 Ni10 C0.5 and Fe74.5 Mn25 C0.5 ). It was found that all three alloys exhibited similar ductility at 298 K. The MEA has the highest yield strength and lowest ultimate tensile strength (UTS) at 298 K and 77 K, and the Fe74.5 Cr15 Ni10 C0.5 alloy has the highest UTS, followed by Fe74.5 Mn25 C0.5 alloy. The MEA's ductility increase when temperatures decrease from 298 K to 77 K, in contrast to its subsystems steels, which had decreasing ductility. As a result, the MEA has the highest product of UTS and ductility (∼75 GPa·%) at 77 K. The twinning-induced plasticity was dominant in the MEA, while deformation-induced martensitic transformation from FCC to body-centered-cubic (BCC), and from FCC to hexagonal-close-packed (HCP) was dominant in Fe74.5 Cr15 Ni10 C0.5, and Fe74.5 Mn25 C0.5 alloys, respectively. In addition, Fe74.5 Cr15 Ni10 C0.5 alloy has the best corrosion resistance, followed by the MEA and Fe74.5 Mn25 C0.5 . Highlights: Mechanical and corrosion behavior of FeMnCrNiC MEA with steels was compared. The FeMnCrNiC has the highest yield strength at both 298 K and 77 K. The order of tensile strength at 298K and 77K is: FeMnCrNiC < FeMnC < FeCrNiC. The order of corrosion resistance is: FeMnC < FeMnCrNiC < FeCrNiC. The mechanical and corrosion mechanism of the three alloys were studied.